Neural tube defects and impaired neural progenitor cell proliferation in Gβ1‐deficient mice - Hiroaki Okae; Yoichiro Iwakura (2010)
Abstract Heterotrimeric G proteins are well known for their roles in signal transduction downstream of G protein–coupled receptors (GPCRs), and both Gα subunits and tightly associated Gβγ subunits regulate downstream effector molecules. Compared to Gα subunits, the physiological roles of individual Gβ and Gγ subunits are poorly understood. In this study, we generated mice deficient in the Gβ1 gene and found that Gβ1 is required for neural tube closure, neural progenitor cell proliferation, and neonatal development. About 40% Gβ1 −/− embryos developed neural tube defects (NTDs) and abnormal actin organization was observed in the basal side of neuroepithelium. In addition, Gβ1 −/− embryos without NTDs showed microencephaly and died within 2 days after birth. GPCR agonist‐induced ERK phosphorylation, cell proliferation, and cell spreading, which were all found to be regulated by Gαi and Gβγ signaling, were abnormal in Gβ1 −/− neural progenitor cells. These data indicate that Gβ1 is required for normal embryonic neurogenesis. Developmental Dynamics 239:1089–1101, 2010. © 2010 Wiley‐Liss, Inc.